The Teacher's Role in Implementing Cooperative Learning in the Classroom
X, 267 p.
Keywords: Cooperative learning is widely endorsed as a pedagogical practice that promotes student learning. Recently, the research focus has moved to the role of teachers’ discourse during cooperative learning and its effects on the quality of group discussions and the learning achieved. Although the benefits of cooperative learning are well documented, implementing this pedagogical practice in classrooms is a challenge that many teachers have difficulties accomplishing. The Teacher's Role in Implementing Cooperative Learning in the Classroom provides readers with a comprehensive overview of the challenges and issues with clear guidelines on how teachers can embed cooperative learning into their classroom curricula to obtain the benefits widely attributed to this pedagogical practice. It does so by using language that is appropriate for both novice and experienced educators. The volume provides: an overview of the major research and theoretical perspectives that underpin the development of cooperative learning pedagogy; outlines how specific small group experiences can promote thinking and learning; discusses the key role teachers play in promoting student discourse; and, demonstrates how interaction style among students and teachers is crucial in facilitating discussion and learning. The collection of chapters includes many practical illustrations, drawn from the contributors’ own research of how teachers can use cooperative learning pedagogy to facilitate thinking and learning among students across different educational settings.